HUBUNGAN ASUPAN MAKANAN DENGAN KEJADIAN PREMENSTRUASI SINDROM PADA SISWI KELAS XI SMA NEGERI 1 PERBAUNGAN - Mawaddatul Husna; Fitri Ardiani; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
One of disturbanees related to menstruation is premenstruation syndrome which is all indication felt towards menstruation disturb dialy activities. Teenager’s low consumption of nutrient essense is one of the factors which causes premenstruation syndrome. This research was conducted to find out the relation of food consumption and premenstruation syndrome to students of XI of SMA Negeri 1 Perbaungan. Research design used is descriptive analytical research with cross sectional by interviewing and using questionaires conducted to students of XI of SMA Negeri 1 Perbaungan. Methods of data analysis based on chi-square test. From the research finding, it was found out that most of students with good consumption of calcium nutrient essense (41,4%), and low consumption of magnesium (55,7%), and more consumption of vitamin B6 (35,7%). Of to students, 40 students (57,1%) have premenstruation syndrome. There is no significant relation between the total of calcium and magnesium consumption and prementruation syndrome based on chi-square test with p(0,261) and p(0,317). There is significant relation between the consumption of vitamin B6 and premenstruation syndrome based on chi-square test with p(0,035). It’s suggested for students of XI to consume high magnesium nutrient essense food because most of the students are lacking of the nutrient essense and their continued research to look at the internal factors and external factors and also inhibiting nutrients associated with premenstruation syndrome. Keywords        : premenstruation syndrome, calcium, magnesium, vitamin B6